High Degree AV Block in Infants - Cahyono, Agus (Jurnal Kardiologi Indonesia, 2025)
In “High Degree AV Block in Infants” (Indonesian Journal of Cardiology, 43(3), 116-22. https://doi.org/10.30701/ijc.1244), there are errors noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1244. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. An error also appears in the affiliation section. In the original publication, the affiliation were incorrectly listed as “Faculty of Medicine, Universitas Surabaya, Surabaya, Indonesia”. The affiliations have been corrected to “Department of Clinical Medicine, Faculty of Medicine, Universitas Surabaya, Surabaya, Indonesia”. The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1244